An honest love: a hearts of Middlefield novel (Hearts of Middlefield, 2, 2010)
Description Not Provided

A hand to hold: a Hearts of Middlefield novel (Hearts of Middlefield, 3,, 2010)
Description Not Provided

A man of his word: a hearts of Middlefield novel (Hearts of Middlefield, 1,, 2009)
When Amish wife Moriah Miller is abandoned by her husband, she fears that she'll never find a man of his word. What Moriah doesn't know is that Levi's twin, Gabriel, has loved her for years. Moriah must learn to accept his love so that she can be made whole again.